Hospital and mid-term results of simultaneous correction of coronary and carotid arteries - A. V. Marchenko; A. S. Vronskiy; P. A. Myalyuk; P. V. Lazarkov; Yu. S. Sinelnikov (Евразийский Кардиологический Журнал, 2021)
Study objective: to present the immediate and mid-term results of onestage surgical treatment of patients in the volume of CEE and CABG based on a differentiated approach to patient selection.Materials and methods: in FCCVS n.a. S.G. Suhanov, Perm developed an algorithm for choosing treatment tactics in patients with combined atherosclerotic lesions of the coronary and brachiocephalic arteries. According to this algorithm, for the period from 01.07.2014-01.01.2021, one-stage correction of CABG + CEE was performed in 104 patients. The primary endpoints were all-cause death, acute myocardial infarction (MI), transient ischemic attack (TIA), and stroke. Hospital and midterm results were analyzed. The average follow-up time in the study of mid-long-term results was 40.3 ± 20.4 months.Results: in the study of hospital outcomes, the mortality rate was 0%. There were recorded 3 (2.9%) cases of perioperative stroke and 1 (0.9%) case of myocardial infarction. There were no cases of TIA. The combined endpoint (death, acute MI, stroke, TIA) reached 4 (3.8%) patients. In the study of mid-term results, we were able to contact 96 patients out of 104 operated on (92.3%). The survival rate was 94.8%. 5 (5.2%) people died. There were 2 (2.1%) cases of myocardial infarction, 4 (4.1%) cases of stroke.Conclusions: simultaneous revascularization of the carotid and coronary regions of CABG + CEE is safe and allows adequate elimination of the lesion in both regions.